Correlation between admission hypoalbuminemia and postoperative urinary tract infections in elderly hip fracture patients - Wei Yao; Wanyun Tang; Wei Wang; Qiaomei Lv; Wenbo Ding (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose This study aimed to evaluate the correlation between hypoalbuminemia upon admission and the incidence of postoperative urinary tract infections (UTIs) in elderly patients with hip fractures. Methods A retrospective analysis was performed on the medical records of elderly patients who underwent surgical treatment for hip fractures at a level I trauma center from 2013 to 2023. Serum albumin levels were measured upon admission, and hypoalbuminemia was defined as a total albumin level < 35 g/L. Multivariable logistic regression and propensity score matching analysis were utilized to control and reduce potential confounding factors, aiming to obtain adjusted odds ratios (ORs) and 95% confidence intervals (CI) for UTIs to determine the strength of the association. Results This observational cohort study included 1279 patients, among whom 298 (23.3%) developed UTIs. Patients with albumin levels < 35 g/L had significantly greater odds of developing UTIs compared to those with albumin levels ≥ 35 g/L (OR 1.86, 95% CI 1.28–2.70). Further analysis, dividing albumin levels into quartiles, demonstrated that patients in the Q2 group (38.0–40.9 g/L; OR 1.38, 95% CI 0.88–2.17), Q3 group (35.0–37.9 g/L; OR 1.69, 95% CI 1.06–2.71), and Q4 group (15.3–34.9 g/L; OR 2.67, 95% CI 1.61–4.43) had notably higher odds of developing UTIs compared to those in the Q1 group (41.0–52.0 g/L). Conclusions The presence of hypoalbuminemia upon admission in elderly patients undergoing hip fracture surgery is strongly correlated with the occurrence of postoperative UTIs. Furthermore, this association exhibits a clear dose–response relationship.